2016
DOI: 10.1158/2326-6066.cir-15-0231
|View full text |Cite
|
Sign up to set email alerts
|

T Cells Expressing CD19/CD20 Bispecific Chimeric Antigen Receptors Prevent Antigen Escape by Malignant B Cells

Abstract: The adoptive transfer of T cells expressing anti-CD19 chimeric antigen receptors (CARs) has shown remarkable curative potential against advanced B-cell malignancies, but multiple trials have also reported patient relapses due to the emergence of CD19-negative leukemic cells. Here, we report the design and optimization of single-chain, bi-specific CARs that trigger robust cytotoxicity against target cells expressing either CD19 or CD20, two clinically validated targets for B-cell malignancies. We determined the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
394
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 498 publications
(406 citation statements)
references
References 45 publications
4
394
0
8
Order By: Relevance
“…Additionally, engineering CAR T cells to express more than one CAR may lessen the ability of tumor cells to downregulate surface proteins targeted by monospecific CAR therapies. The development of bispecific CAR T cells, such as those that recognize both CD19 and CD20, another generally B-cell-specific surface antigen, may increase response rates and improve durability of responses by preventing antigen-loss tumor escape mechanisms [66,67].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, engineering CAR T cells to express more than one CAR may lessen the ability of tumor cells to downregulate surface proteins targeted by monospecific CAR therapies. The development of bispecific CAR T cells, such as those that recognize both CD19 and CD20, another generally B-cell-specific surface antigen, may increase response rates and improve durability of responses by preventing antigen-loss tumor escape mechanisms [66,67].…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical and early-phase clinical studies have shown that targeting multiple antigens in CAR-T-cell therapy can prevent antigen loss relapses. For example, CAR-T cells targeting CD19/CD20, CD19/CD22, or CD19/CD123, can also improve the extremely limited options and poor outcomes of patients with CD19-negative relapses [58][59][60]. Attention should also be paid to the uncontrolled proliferation of CAR-T-cell therapies.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…Such TanCAR induces a T cell response upon engagement of either antigen; both antigens are not needed to be simultaneously present on the same cell to initiate CAR T cell activation. With this respect, CD19-CD20 bispecific CARs were engineered in order to mitigate a B cell leukemia relapse through cells which lost either antigen [49]. In particular, leukemia relapses occurred upon therapy with CD19 CAR T cells, and the relapse is predominantly driven by CD19 − CD20 + leukemic cells which are likely recognized by CD19-and CD20-specific TanCAR T cells.…”
Section: Car T Cells Recognizing Multiple Antigensmentioning
confidence: 99%